Perencanaan Aplikasi E-Commerce “Lokanara” Berbasis Web dengan Terverifikasi Produk berbasis QR - Rangga Galih Wardani; Arya Kusumadewa; Rafi Nabil Bahtiar; Alya Nur Samiya (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Advances in digital technology encourage Micro, Small, and Medium Enterprises (MSMEs) to integrate digital platforms in order to expand the reach of product marketing. This digital transformation provides a great opportunity for MSMEs to reach a wider range of consumers, both in the national and international markets. By utilizing technology, MSMEs can increase marketing effectiveness, speed up transactions, and strengthen brand image. However, the main challenge faced is the low level of consumer confidence in the authenticity, quality, and legality of local products. The number of counterfeit products in the online market and the lack of verified information are serious obstacles that can reduce the competitiveness of MSMEs in the midst of global competition. This research aims to design and develop an e-commerce platform called "Lokanara", which is specifically designed to support MSMEs in marketing local products safely, efficiently, and verified. The Lokanara system is equipped with a QR Code-based product verification feature, allowing consumers to check the authenticity of products quickly and accurately. In addition, user authentication is carried out using the Session Based Authentication method to ensure the security of data and transactions. The platform is also integrated with the Midtrans payment gateway, which supports various digital payment methods with a high level of security and ease of transaction processing. The system development methodology includes analyzing user needs, designing system schemas using Unified Modeling Language (UML), to the implementation stage on web-based platforms. The testing process is carried out using the black box testing method to ensure that all features function according to specifications. The test results show that Lokanara is able to increase the transparency of product information, build consumer trust, and help MSMEs maintain the credibility and competitiveness of local products. With these innovative features, Lokanara has the potential to become a trusted and inclusive e-commerce solution that drives the growth of the digital commerce ecosystem in Indonesia.